Assessment of the fate and effect of ivermectin in a simulated aquaculture ecosystem. (21st November 2019) - Wang, Di; Han, Bing; Li, Shaowu; Du, Xue; Cao, Yongsheng; Lu, Tongyan
Abstract: As a potent anti‐parasitic agent, ivermectin (IVM) has been commonly used by the aquaculture industry. In this study, the environmental fate and effects of IVM in a simulated aquaculture ecosystem were evaluated. The simulated ecosystem was composed of water, sediment, aquatic plants, invertebrates and fish. According to the new fishery drugs manual, IVM was introduced into the water at a final concentration of 1.6 × 10 –4  mg·L –1 . The samples, including the roots and leaves of aquatic plants, the visceral mass and muscle of fish, the soft tissue of mud snails, sediment and water were collected at 0.5 hr, 1, 7, 15, 30, 45, 60 and 70 days after the treatment. Our results indicated that IVM was distributed quickly and widely into the whole ecosystem and accumulated to high levels in organisms resulting in residues that persisted for a long time. The IVM concentration in the sediment increased continuously and reached a peak (2.896 ng·g –1 ) at 30 days. Moreover, the concentration of IVM in the water declined from 0.5 hr to 1 day and then increased to a peak of 0.130 ng·mL –1 at 7 days. The IVM concentrations in the fish reached a peak in muscle (192.10 ng·g –1 ) and visceral mass (259.82 ng·g –1 ) at 7 days. IVM was quickly accumulated by the aquatic plants, and it was found at higher levels in the leaves than in the roots. The IVM concentration in the mud snails reached its peak with a value of 24.750 ng·g –1 at 7 days and then decreased quickly at 15 days. It was notable that a second peak of IVM accumulated in the fish and aquatic plants after 30 days. The aquaculture ecosystem simulated in this study was feasible and effective and could be applied to assess the fate of IVM in aquatic environments.